Strategi Pengembangan BUMDesa Melalui Optimalisasi Lahan Desa sebagai Upaya Peningkatan Pendapatan di Desa Turi Kecamatan Turi, Kabupaten Lamongan - Wahyu Eko Sapuhtra; Widyawati Widyawati; Nihayatus Sholicah (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This article discusses the development strategy of Village-Owned Enterprises (BUMDesa) through the optimization of village land in Turi Village, Turi District, Lamongan Regency, as an effort to sustainably increase village income. The potential of village land, including agricultural, fishery, and marginal lands that have not been utilized optimally, serves as the main focus for economic development initiatives. A qualitative approach with case study methodology is employed to explore in-depth the strategies, challenges, and opportunities faced by Turi BUMDesa in managing these assets. The study emphasizes the importance of professional, innovative, and participatory asset management supported by collaboration among stakeholders such as local government, community members, BUMDesa managers, and the private sector. Through identifying unique land potential, market analysis, and developing innovative business models such as agro-tourism, integrated agriculture, and renewable energy, BUMDesa is expected to create productive and sustainable economic activities. The main challenges include low land utilization, limited institutional capacity, and minimal innovation in business management. Therefore, capacity building, innovative business development, and strengthening cooperation are key to the success of this strategy. The development of BUMDesa based on land optimization in Turi Village is expected to enhance local income, strengthen community economic independence, and open new employment opportunities for villagers. Overall, this article emphasizes that proper and innovative asset management is crucial for achieving sustainable village development and improving community welfare evenly.